Effectiveness of the E-Katalog System in Supporting the Procurement Process of Goods and Services - Thalia Devega Tires; Insanita Qona'ah; Arief Hertadi Rustam; Debi Irawan; Ismail Ismail (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This research investigates the effectiveness of the E-Catalog system in supporting goods and services procurement at Sesko TNI Bandung. As a digital procurement platform introduced by the government, the E-Catalog aims to increase transparency, accuracy, and process efficiency. Despite these intended advantages, its adoption remains constrained by users’ limited familiarity with digital procurement practices and their long-standing reliance on manual procedures. To address this issue, the study applies the Technology Acceptance Model (TAM) as the analytical framework, focusing on perceived usefulness, perceived ease of use, user attitudes, and behavioral intentions toward system utilization. A mixed-methods approach with a sequential explanatory design was employed. The quantitative phase involved distributing structured questionnaires to procurement personnel to measure key variables related to system acceptance. Subsequently, qualitative data were obtained through in-depth interviews with procurement operators to clarify and deepen the interpretation of statistical results. The study finds that perceived usefulness and perceived ease of use significantly shape user attitudes and intention to utilize the E-Catalog. These variables collectively contribute to improving the overall effectiveness of the procurement process. The results highlight that the more users perceive the system as beneficial and easy to operate, the more likely they are to adopt it consistently, thereby enhancing operational efficiency at Sesko TNI Bandung. This research underscores the importance of increasing digital literacy, strengthening system socialization, and providing continuous training to optimize the performance of the E-Catalog platform.